Direito dos povos e comunidades tradicionais de terreiro: reflexões sobre a discriminação racial às religiões de matriz africana em São Luís do Maranhão - SEREJO, Jorge Alberto Mendes (2017)
The present work presents the sociojuridic categorization of the tradicional peoples and communities of terreiro as a modality of traditional peoples and communities that have emerged in the national political scene since the 1970s, constituting the so-called "new" social movements. It shows how specific territorialities of these units of mobilization led to changes in the national legal scenario, increasing rights and disputing positions in the legal field. It undertakes an investigation of how the struggle for the right to recognition terreiro’s peoples has been transformed into the fight against racism and how these discussions intersect the issue of religious freedom. At this point, the right to religious freedom is presented as a liberal legacy, which in Brazil has coexisted with racial terror and the coloniality of knowledge and power, responsible for erasures that lead daily to the discrimination of African religious practices belonging to minorities ethnic groups. These theoretical reflections invite a re-reading of the notion of racism and religious intolerance from decolonial perspectives, leading to the categorization of the right to religious freedom of terreiro’s peoples and communities as ethnic rights. Based on the experience of Pai Tico, from the Terreiro Ilê Axé Oyá Sapatá, a theoretical and methodological reflection was sought to investigate the deletions and the prohibitions that have hampered or impeded the knowledge, by the local Judiciary, of cases of violation of rights ethnic and racial groups of traditional peoples and communities of terreiro, especially in those violations resulting from racial discrimination based on religious motivation under the Law nº. 7.716/89 (Lei “Caó”).